1993
DOI: 10.2466/pms.1993.76.3.995
|View full text |Cite
|
Sign up to set email alerts
|

Students' Perceptions of the Value of Teaching Evaluations

Abstract: This research examined how 187 students assessed a course evaluation form, the anonymity of the evaluation process, the fairness and accuracy students attribute to the task of completing evaluations of instruction, and students' perceptions of the extent to which teachers and administrators make use of the information provided by evaluations. 92% of the student-participants believed that the rating forms provided an effective means of evaluating instruction. The majority thought instructors pay attention to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…What do we know of the process used by students to respond to student rating items? Although there have been several studies (Marlin, 1987;Dwinell and Higbee, 1993;Ballantyne, 1998) of student attitudes about student ratings, we still know very little about the actual process students follow when responding to rating forms. Do students respond to items by comparing the instructor's performance to that of other instructors or to some idealized standard?…”
Section: Examining the Validation Of Student Ratings And The New Valimentioning
confidence: 99%
“…What do we know of the process used by students to respond to student rating items? Although there have been several studies (Marlin, 1987;Dwinell and Higbee, 1993;Ballantyne, 1998) of student attitudes about student ratings, we still know very little about the actual process students follow when responding to rating forms. Do students respond to items by comparing the instructor's performance to that of other instructors or to some idealized standard?…”
Section: Examining the Validation Of Student Ratings And The New Valimentioning
confidence: 99%
“…Felton, Mitchell and Stinson (2004) suggested that students tend to rate better for instructors who is attractive for them. In contrast, the elderly instructors are more likely to get less rating (Gezgin, 2011 (2001), Dwinell & Higbee (1993) found that students believed that their assessments were an effective mean of voicing their opinions about instructors' teaching. Several factors such as the level of the class being taught, students' interest in the subject matter before enrolling in the class, the size of the class, the gender, the grades, the rigor of the course, the instructor's warmthinducing behaviour, students' characteristics, instructor characteristics, course difficulty and other characteristics can potentially affect an instructor's evaluation by the students (Martin, 1998;Greenwald & Gillmore, 1997;Marsh, 1987;Habson & Talbot 2001).…”
Section: Views On Set Implementationmentioning
confidence: 87%
“…Also, the placement of such authority in the hands of students may be problematic for other reasons, but there is a paucity of research from the students' perception. Dwinell and Higbee (1993) surveyed over 150 students to gather opinions regarding the value of teaching evaluations. They observed that 67 percent of the respondents believed that rating forms were an effective means of evaluating instructors, and 83 percent believed that instructors changed their behavior as a result of weaknesses identified by the evaluations.…”
Section: Student Perceptionsmentioning
confidence: 99%